Mesocyclops longisetus (THIÉBAUD, 1912) as biological control of aedes aegypti (linnaeus, 1762) larvae in simulated environment - Pires, Stefani; Yoshimura, Ingrid; Gomes, Thayllon Orzechowsky; Neves, Gilmar Perbiche (Revista Hipótese, 2019)
The dipter Aedes aegypti is a transmitter of at least three important diseases in Brazil and for this reason it started to develop some preventive measures, mostly about the water accumulation, that shows a great potential to its reproduction and proliferation. Others mechanisms like the biological control method are not frequently used in Brazil and in this study we tested the use of a copepod crustacean (Mesocyclops longisetus) as a predator of Aedes aegypti larvae (Culicidae: Diptera). The copepod Mesocyclops, as the most Cyclopoids, has a short life cycle, the females produce about 100 eggs during the shelf-life, and it can withstand a wide range of thermal variations and being capable to get in quiescence when exposed to unfavorable conditions. Many copepods and larvae proportions were separated and added in aquariums to be observed during five days, the first stage larvae were exterminated. The second stage larvae were less eaten than the first stage larvae and the others stages weren’t consumed by the copepod. The results indicate that the Mesocyclops longisetus can be used to control larvae of A. aegypti of the first and second stage but it is ineffective in others stages even when the prey density is high.